Analyzing the Factors that Effect Maximum Time to Repair Thermal Energy Systems in Cold/Arctic Climates - Oberg Bjorn; Urban Angela; Leffel Emmett; Goebel Jonathan; Perry Matthew; Vas Dragos; Broderson Dayne; Liesen Richard; Zhivov Alexander (E3S Web of Conferences, 2021)
Resilient energy systems are those that can prepare for and adapt to changing conditions, and recover rapidly from disruptions including deliberate attacks, accidents, and naturally occurring threats. This makes thermal energy systems resilience especially important in extreme climates such as arctic or tropical environments. While metrics and requirements for availability, reliability, and quality of power systems have been established (DoD 2020), similar metrics and requirements for thermal energy systems are not well understood. In one of the first attempts to address this deficiency, a study was conducted to better understand the factors that affect maximum time to repair thermal energy systems. Maximum time to repair of thermal systems can be defined in terms of how long the process can be maintained or the building remains habitable or protected against damage from freezing of water pipes, sewer, fire suppression system, protect sensitive content, or start growing mold during extended loss of energy supply with extreme weather events. The purpose of this paper is to present the methodology and results of a novel temperature decay test conducted during the winter, along with blower door tests on five representative military buildings in Alaska. The results from the field tests described in this paper show that the distribution of temperature decay is not uniform throughout the building and that it will vary depending on solar position, building features and wind direction. This demonstrates that strategic placement of personnel, equipment and facilities that are critical to building operations, can extend operation time during a thermal energy disruption.